Structural monitoring detection using global positioning system - Shu, Kian Kok (2017)
Many man-made structures such as high rise building undergo various forms of deformation and it requires mitigation measures to understand the causes and mechanism of deformation. Global Positioning System (GPS) is utilised for positioning in three dimensional and has been used to monitor deformation magnitude of structure. The GPS Real Time Kinematic (GPS RTK) and Static are part of GPS positioning methods. GPS static in high accuracy, able to observe in all weather conditions and no requirement for inter-visibility, with aids of internetworking services can provide the near real time result in observation. The limitation on GPS RTK in radio link communication such as the canopy obstruction between base and rover stations will interrupt communication. The objective of study is to investigate the implementation of structural monitoring system using GPS for deformation analysis on structure in near real time. Data transmission of GPS Static between monitoring stations and central processing unit is using internetworking services. The significant role of GPS static survey in identification of structural stability has been studied and explored, with the evaluation focuses on session length in structural monitoring and network configuration. The developed system consists of planning and preparation of GPS survey, GPS baseline reduction, network adjustment and deformation processing as incorporated in GPS Static Adjustment and Deformation Detection (GPS STAAD). The accuracy and reliability of GPS STAAD have been verified with other resources, namely GPSAD2000 and NETGPS and the result shown all the points in the network are stable. This result has been tested in simulation test and shown that a deformation movement of up to 20mm level has be detected by the program. In conclusion, feasibility of applying the GPS Static method in structure monitoring, as well as implementation of structural monitoring system is successfully studied.